Lazarus. Volume 5, Cull - Rucka, Greg (Image Comics, 2017)
"The world now lies divided not amongst political or geographic boundaries but amongst financial ones. Wealth is power, and that power rests with only a handful of families. And now those families are at war. As warring Lazari battle across the theater of Western Europe, Forever Carlyle has been sidelined, recovering from grievous wounds suffered during the Battle of Duluth. Physical trauma can be quickly healed-- it is the damage to her heart that festers, infected and growing. There is now no trust between her and her father, Malcolm Carlyle." --